Upper limb exercise for haemodialysis fistula surgery - Heiwe, Susanne (Cochrane Database Syst Rev, 2021)
Title reassignment. New protocol has been published.  Reanpang  T, Prasannarong  M, Pongtam  S, Murray  ST, Rerkasem  K. Upper limb exercise for people on haemodialysis following arteriovenous fistula surgery. Cochrane Database of Systematic Reviews 2019, Issue 5. Art. No.: CD013327. DOI: 10.1002/14651858.CD013327. Accessed 18 March 2021.